Bisexuality in Bohemian Rhapsody: A Queer Study - Syabilla Maylya; Mamik Tri Wedawati (Surakarta English and Literature Journal, 2022)
This research was meant to describe the shape of sexuality in Bryan Singer's "Bohemian Rhapsody" (2018) by analyzing the main character from the Queer perspective. Bisexual is a term used to describe relationships of people both with the same sex and the opposite sex for a certain period, including being attracted to or having sexual activity. Bohemian Rhapsody discusses Queen's career journey by showcasing the lead singer as a highlight. Freddie struggles to live in a world of hedonism and stigma, preconceptions, and the erasure of Bisexuality as a social identity. It will answer how to construct binary desires and how society shapes them by applying theory from Butler's work "Gender Trouble." to fulfil this study; In this study, either textual or visual film analysis will be applied to the subsequent discussion. 1.) Determine forms of Bisexuality in Bohemian Rhapsody; 2.) Reveal Bisexuality towards the character interactions in Bohemian Rhapsody. Through this interpretation, bisexual visibility is frequently devalued and forced to join monosexism with similar terms such as gay and lesbian, resulting in the erasure of Bisexuality. This behaviour is predicated on the social and cultural stereotypes attached to "bisexual."